2007
DOI: 10.1111/j.1542-4758.2007.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and limitations of maintenance hemodialysis in urban South India

Abstract: Maintenance hemodialysis is a treatment modality available to few patients reaching end-stage renal disease in India. However, the morbidity and outcome of such treatment remains largely unknown. A retrospective cohort of patients commencing hemodialysis in a secondary care institution in India between January 1, 2002 and December 31, 2004 was studied. Patient demographics, cardiac status, access, hospitalizations, and emergency room visits were assessed and outcomes determined. During the study period, 95 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
4
13
1
Order By: Relevance
“…Lower mean age and male predominance were traits observed in both the groups reflecting the sociocultural influence of health seeking behavior, rather than a gender difference, as reported previously. [4569] High prevalence of AVF in our study is consistent with previously reported cohorts from India. [610] Diabetic patients were higher in the 3x group aligned with a high prevalence of diabetes in CKD population.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Lower mean age and male predominance were traits observed in both the groups reflecting the sociocultural influence of health seeking behavior, rather than a gender difference, as reported previously. [4569] High prevalence of AVF in our study is consistent with previously reported cohorts from India. [610] Diabetic patients were higher in the 3x group aligned with a high prevalence of diabetes in CKD population.…”
Section: Discussionsupporting
confidence: 91%
“…[11] The follow-up period for patients in this study may appear short, but it is not insignificant given the duration of survival reported in patients on HD in India. [56] A small proportion of our patients had third party payers reflective of the existing practice patterns and consequential constraints in the delivery of care. There is a trend toward a higher proportion of privately insured patients in the 3x category, which reflects the choice of HD frequency is influenced by payer category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Indian prospective single-center study of 96 patients on MHD in a private tertiary care center reported a 2-year mortality rate of 19.8% [12]. Another retrospective analysis of 95 patients on MHD showed a median survival period of 410 days [13]. Here, we report 5-year survival rates from a large retrospective analysis of 897 patients from different socioeconomic groups who were initiated on MHD in five centers in south India from 2003 to 2009.…”
Section: Discussionmentioning
confidence: 99%